Literature / linguistic / psychiatric psychopoetics: correlation of content aspects (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article continues the cycle of the author's publications, which highlights the problem of psychopoetical discourse in contemporary literary criticism. The content psycho- borders and objects in the literary, linguistic, psychological contexts are generalized and systematized. The circle of problems of psychopoetics as a psychological direction and method of research connected with the specificity of its interdisciplinary science-intensiveness is defined.
Keywords: psychopoetics; psycholinguistics; subject / object of speech; artistic speech; psychiatric literary criticism; characterological and psychopathological analysis of the work